MYC Enhances Cholesterol Biosynthesis and Supports Cell Proliferation Through SQLE - Yang, Fan; Kou, Junjie; Liu, Zizhao; Li, Wei; Du, Wenjing (Frontiers in Cell and Developmental Biology, 2021)
Oncogene c-Myc (referred in this report as MYC) promotes tumorigenesis in multiple human cancers. MYC regulates numerous cellular programs involved in cell growth and cell metabolism. Tumor cells exhibit obligatory dependence on cholesterol metabolism, which provides essential membrane components and metabolites to support cell growth. To date, how cholesterol biosynthesis is delicately regulated to promote tumorigenesis remains unclear. Here, we show that MYC enhances cholesterol biosynthesis and promotes cell proliferation. Through transcriptional upregulation of SQLE, a rate-limiting enzyme in cholesterol synthesis pathway, MYC increases cholesterol production and promotes tumor cell growth. SQLE overexpression restores the cellular cholesterol levels in MYC knockdown cells. More importantly, in SQLE-depleted cells, enforced expression of MYC has no effect on cholesterol levels. Therefore, our findings reveal that SQLE is critical for MYC-mediated cholesterol synthesis, and further demonstrate SQLE maybe a potential therapeutic target in MYC-amplified cancers.